PELATIHAN PADA IBU BAYI UNTUK MENCEGAH MALNUTRISI DENGAN TEKNIK BABY MASSAGE DI DUKUH NUSUPAN DESA KADOKAN KECAMATAN GROGOL KABUPATEN SUKOHARJO - Silviana Rahmawati Ekaputri; Nabila Windi Aulia; Zahrani Bakhita Hanifah; Devina Dara Safitri; Nera Bela Beauty Nur; Sevia Yayustika Qoirunnisa; Silviana Dian Putri Ichsani; Nida Zahrotul Ummah; Jami'atulhita Alfirizqi; Wildan Prima Jalu Prasojo; Ziddan Arif Darmawan; Noor Alis Setiyadi; Dian Hudiyawati (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2024)
Malnutrition or malnutrition is still common in Kadokan Village because babies who have difficulty eating cause babies to lack intake of carbohydrates, protein, fat and vitamins so babies have difficulty gaining weight. Providing stimulation to babies can be used as a solution to overcome these problems.  The purpose of doing this service is to increase mother's knowledge and understand about the types of foods that contain nutrients in amounts that are in accordance with the needs of toddlers and monitor body weight regularly and baby massage training to improve mother's abilities so that they can know the ways and benefits of baby massage which is one of the stimuli to maintain normal baby weight according to age. The method used in this service is baby massagec ounseling and direct training. The result of this service is that there is an increase in the knowledge and abilities of baby mothers which can be seen from the results of the pretest and posttest. The conclusion from this service is that the knowledge and abilities of the baby'smother have increased in this baby massage training. Suggestions for parents of babies can seek information and further increase knowledge in terms of infant massage and for further activities to carry out activities in collaboration with village midwives or village officials to develop these activities with different methods or designs